2019
DOI: 10.1002/mabi.201900042
|View full text |Cite
|
Sign up to set email alerts
|

Mannose‐Modified Serum Exosomes for the Elevated Uptake to Murine Dendritic Cells and Lymphatic Accumulation

Abstract: The surface of bovine serum‐derived exosomes (EXOs) are modified with α‐d‐mannose for facile interaction with mannose receptors on dendritic cells (DCs) and for efficient delivery of immune stimulators to the DCs. The surface of the EXOs is modified with polyethylene glycol (PEG) without particle aggregation (≈50 nm) via the incorporation of 1,2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine (DSPE) into the lipid layer of the EXO, compared to chemical conjugation by N‐hydroxysuccinimide activated PEG (NHS‐PEG). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 61 publications
(85 reference statements)
0
63
0
Order By: Relevance
“…In particular, for what concerns the functionalization, it is important to find the proper molecule for the desired purpose, and a variety of functionalizations are reported in the literature, as mentioned above. As for the indirect methods, the use of DSPE-PEG [ 88 , 89 , 100 ] or DMPE-PEG [ 87 ], as spacer to expose the functionalization, is a commonly used strategy. Finally, for both in vitro and in vivo testing steps, the biological challenges are the same listed above and analyzed for the indirect methods in terms of choice of the best cell line and/or animal model.…”
Section: Engineered Evsmentioning
confidence: 99%
“…In particular, for what concerns the functionalization, it is important to find the proper molecule for the desired purpose, and a variety of functionalizations are reported in the literature, as mentioned above. As for the indirect methods, the use of DSPE-PEG [ 88 , 89 , 100 ] or DMPE-PEG [ 87 ], as spacer to expose the functionalization, is a commonly used strategy. Finally, for both in vitro and in vivo testing steps, the biological challenges are the same listed above and analyzed for the indirect methods in terms of choice of the best cell line and/or animal model.…”
Section: Engineered Evsmentioning
confidence: 99%
“…The further functionalization of distal end of PEG chain with appropriate targeting ligands, as already described for synthetic particles [53], can easily overcome this drawback and create a promising tool for drug delivery with stealth properties and targeting abilities. A very recent study [54] described how modify EVs' surface with the active targeting ligand mannose. Exosomes' surface was successfully modified with PEG, avoiding particle aggregation, through the incorporation of 1,2-distearoyl-sn-glycero-3-phosphoethanolamine (DSPE) into the lipid layer of the exosome.…”
Section: Chemico-physical Functionalizationmentioning
confidence: 99%
“…Exosomes' surface was successfully modified with PEG, avoiding particle aggregation, through the incorporation of 1,2-distearoyl-sn-glycero-3-phosphoethanolamine (DSPE) into the lipid layer of the exosome. For targeting purposes, the PEG's distal end, functionalized with amine groups, was further conjugated with mannose-isothiocyanate, guaranteeing a better accumulation of functional exosomes in lymph-nodes [54].…”
Section: Chemico-physical Functionalizationmentioning
confidence: 99%
“…On the other hand, also cell-secreted sEVs can be considered attractive candidates to specifically target M2-like macrophages via the MR, since they expose high mannose and other classes of N-linked oligosaccharides on their surface [ 115 , 116 ].…”
Section: The Mannose Receptor In M1 Polarizationmentioning
confidence: 99%
“…Glycomic studies conducted to date demonstrate that surface glycoprofiles of sEVs contain high amounts of mannose and other classes of N-linked oligosaccharides [ 27 , 34 , 128 , 129 ] making them suitable ligands for the MR. Recently, it has also been shown that mannose-modified serum sEVs display elevated uptake by murine DCs [ 116 ]. This evidence, together with a number of studies showing that mannosylation of both liposomes [ 102 ] and synthetic nanocarriers [ 130 , 131 ] enhance cellular uptake by M2 macrophages, inducing stimulation and polarization of macrophages toward the M1 phenotype, point to sEVs as powerful ligands of M2 macrophages.…”
Section: Extracellular Vesicles For Anti-tumor Therapymentioning
confidence: 99%